A multi-user virtual reality experience for space missions. Issue 2 (June 2021) - Mastro, A. Del; Monaco, F.; Benyoucef, Y.
Abstract: Simulations in augmented (AR) and virtual reality (VR) environments are increasingly part of space programs studying human-crewed missions to Moon and Mars. The goal of these simulation programs is to both train crews and study human behaviour in extreme conditions environments. A virtual multiuser experience (VMUE) consists of the virtual simulation of knowledge shared by at least two users interacting with each other and with the surrounding critical environment. In the space sector, VMUE is a relatively low cost means of simulating the concurrent activities of astronauts interacting with a simulated space environment that can be rolled out right from the start of the project. Applications include training in exploration, maintenance and inspection, ground/space station communication, command and control task execution on robotic systems, and most importantly, crisis resource management (CRM) with situational awareness training in safety analysis and risk prevention. The VR multiuser experience can also be combined with AR devices to obtain a wide range of simulation capabilities and collaborative operations in a hybrid environment. Given the critical importance of multiuser experience in VR and AR, this paper aims to offer a short review of the Mars Planet Research Group's activities, namely: High level-of-likelihood reconstruction of entire regions of Mars/Moon to be used in the VR environment; Development and combination of the two VR treadmills - MOTIVITY and MOTIGRAVITY - for a series of scientific operations and simulations, including physical and medical rehabilitation and education.